1990
DOI: 10.1152/ajprenal.1990.258.6.f1625
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium inhibits glucose uptake in primary cultures of mouse cortical tubule cells

Abstract: We studied the effect of cadmium (Cd2+) on transport of alpha-methylglucoside in primary cultures of mouse kidney cortical tubule cells grown in defined medium. When cultured cells were exposed to Cd2+ concentrations from 0 to 6 microM for 24 h, uptake of alpha-methylglucoside was inhibited in a dose-dependent manner by up to 50%. By contrast, acute exposure of the cells to 7 microM Cd2+ for 60 min did not inhibit alpha-methylglucoside uptake. Increasing Cd2+ concentrations progressively decreased the Vmax of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…The Na+-dependent transports decreased in Vma x without changing the Km value for substrates, thus suggesting that the Cd treatment causes either a decreased number of active transporters or a decreased turnover rate of an unchanged number of transporters, or both, while the affinity for the substrate remains unaffected. Similar conclusions were drawn from the glucose transport data obtained in vitro, in primary cultures of mouse cortical tubule cells treated with Cd [7]. The Na+-independent transport systems in renal cortical basolateral membranes were not affected by Cd treatment [17].…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…The Na+-dependent transports decreased in Vma x without changing the Km value for substrates, thus suggesting that the Cd treatment causes either a decreased number of active transporters or a decreased turnover rate of an unchanged number of transporters, or both, while the affinity for the substrate remains unaffected. Similar conclusions were drawn from the glucose transport data obtained in vitro, in primary cultures of mouse cortical tubule cells treated with Cd [7]. The Na+-independent transport systems in renal cortical basolateral membranes were not affected by Cd treatment [17].…”
Section: Introductionsupporting
confidence: 80%
“…Based on transport and kinetic experiments, previous studies have indicated that glucosuria, aminoaciduria and phosphaturia in Cd-intoxicated rats may result from reabsorptive defects due to a decreased Vmax of the specific carriers in the proximal tubule brushborder membrane [2,7,17,19,20]. This impaired transport may be due to: (1) a loss of carriers in the brush-border membrane [2,7,17,19,20], (2) a direct inhibiton of carriers by Cd, possibly by binding to functionally important sulphydryl groups in membrane proteins [2,5,17,20,30], (3) changes in membrane lipid composition similar to that in experimental ischaemia [22], or (4) direct interaction with membrane phospholipids [30], which may affect the binding capacity of membrane transporters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in doses ranging from 2.5 to 7.5 lM resulted in a dose-dependent decrease of the V max of Na ? -glucose cotransport, without affecting the affinity of the transporters (Blumenthal et al 1990). Kinne et al demonstrated that the inhibition of L-glutamate transport in cortical BBMV isolated from male New Zealand white rabbits, preincubated for 30 min with 1 lM to 1 mM CdCl 2, could be attributed to a marked decrease in the V max of the transport system (half maximal inhibition at 50 lM CdCl 2 ), whereas the affinity for glutamate seemed to increase if it changed at all (Kinne et al 1995).…”
Section: Cadmium Effects On Membrane Transport Of Glucose and Amino Amentioning
confidence: 99%